PEMBERDAYAAN EKONOMI KREATIF MASYARAKAT DESA SIDAKMUTI KECAMATAN SUKARESMI KABUPATEN PANDEGLANG DALAM PEMANFAATAN LIMBAH PLASTIK PADA PEMBUATAN PAVING BLOCK - Bahits, Abdul; Julianthi, Sa'adiyah; Carolina, Carolina; Nurhadi, Hadi; Maulana, Ahmad (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
This community service activity in Sidakmukti Village, Sukaresmi District, Pandeglang Regency aimed to empower the creative economy through the utilization of plastic waste to produce paving blocks. The main problems addressed were the high accumulation of plastic waste in coastal areas and residential neighborhoods, combined with low public awareness of waste management. Using a participatory approach and support from the village head, the community actively collected and recycled plastic waste. An appropriate technology in the form of a plastic waste shredding machine was designed and operated by residents. The shredded plastic waste was mixed with sand to produce paving blocks that meet strength and aesthetic standards. These products are used as material for village access roads. The activity results showed increased awareness, skills, and new economic potential for the community. This empowerment model can be replicated to support sustainable development and environmentally friendly waste management.